A MODEL FOR SUSTAINABLE COMPETITIVE ADVANTAGE IMPROVEMENT OF BATIK SMEs AT CENTRAL JAVA PROVINCE AND DIY (SPECIAL REGION OF YOGYAKARTA) - Erna Indriyaningrum; Olivia Fachrunnisa (School of Business, Bogor Agricultural University (SB-IPB), 2021)
The availablity of Information technology in IR 4.0 demands the ability of SMEs to build a culture to foster competitiveness. This study aims to test a model to improve Sustainability Competitive Advantage based on Innovation Culture, Adaptation Capability and IT Adoption. This type of research uses explanatory research, to test the proposed hypothesis. Data was collected from 106 Batik SMEs owner of Central Java and Yogyakarta through a questionnaire and analysis using SmartPLS. The results shows that SMEs need to strive for the development of an Innovation Culture, in the form of creating new product and services and finding new market opportunities for running their business. Innovation Culture is useful for fostering adaptability in the form of creating change, focusing on services, and developing knowledge. The Innovation Culture that has been formed also has an impact on the ability to apply information technology, namely relative advantage, adaptability, and practicality. Adaptation Capability and Technology Information Adoption that has been formed in SMEs, can help to increase Competitive Advantage so that it continues, marked by increased cost reduction, differentiation and quality. Keywords: sustainable competitive advantage, innovation culture, adaptation capability, technology information adoption